(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The TYR (Tyrosinase) and MC1R (Melanocortin 1 receptor) genes are recognized as important genes involved in plumage pigmentation in Korean native chickens. Specifically, most color patterns in chicken result from differential expression of the TYR gene. In this study, the co-segregation of the pigmentation and sequence of the TYR and MC1R genes was investigated through intercrosses between red (R1q1), red with black and black plumage color types of native Korean chickens. Materials and Methods: Using DNA, RNA, and tissue by plumage color of each Korean native chickens, the role of major genes in pigmentation of pheomelanin was evaluated. Reverse transcription polymerase chain reaction, sequencing, western blot, and immunohistochemical were performed to determine the effect of TYR and MC1R genes on plumage pigmentation in Korean native chickens. Results: The KCO line (Korean chicken Ogol: Black-line) with an EEC _ genotype exhibited black feathers, whereas red and red mixed with black chicken with EeC genotype exhibited white feathers. There were notable differences between the base sequences of MC1R and TYR in three Korean chicken breeds, with the highest variation in TYR. Perhaps this is the key characteristics of Korean chicken. Further, we analyzed the expression patterns of MC1R and TYR genes in each type of Korea native chicken and observed that TYR expression was high in feather follicle (R1q2) of KCO tissue. However, native red (Korean chicken red) and native red with black (Korean chicken red dark) chickens have increased TYR expression in the tissue. However, the expression of MC1R was much different from that of TYR. Conclusion: In this study, our results suggest that the differences in position and TYR expression levels exert more influence on plumage pigmentation in native Korean chicken breeds than changes in MC1R expression levels. J. Adv. Vet. Anim. Res., 8(2): 266-273, June 2021